VALIDITY ASSESSMENT OF OF ENGLISH LEARNING MODULE INTEGRATED WITH POSTER PRESENTATION AND VLOG - Amna, Shally; Rasmita, Rasmita (TELL - US JOURNAL, 2019)
Assessing validity is an essential process in designing a module. This research is a part of on-going research in developing an English learning module for students in Information system department integrated with poster presentation and Vlog techniques. This present study aims at evaluating the validity of the module. Five validators are used to assess the same module. The value of the validation is calculated by using V Aiken (1985). The results shows that the experts’ validation in the module has an average score of validation of 0.889 in the Content component, a score of 0.893 in the Language Understanding component, a score of 0.900 in the Presentation component and a score of 0.833 in the Writing Mechanics component, thus all components are is considered to have a high average validation score from the validation standard score of 0.677 thus the English learning module developed has been valid and can be used with few revision.